The Judgment House - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Judgment House" by Gilbert Parker is a fictional novel likely written in the late 19th century. The story intricately weaves themes of ambition, passion, and social dynamics through the lives of its central characters, particularly focusing on Jasmine Grenfel and Rudyard Byng. As they navigate relationships and societal expectations, the narrative promises a rich exploration of human motivations against a backdrop of artistic and political challenges. At the start of the novel, we are introduced to a vibrant scene at Covent Garden, where the debutante Al'mah captivates the audience with her powerful singing. Among the spectators are Adrian Fellowes, who appears self-satisfied and calculating; Ian Stafford, romantically drawn to Jasmine Grenfel; and Jasmine herself, who is torn between her feelings for Stafford and the allure of Rudyard Byng, a wealthy South African with a magnetic presence. The opera's climax is disrupted when Al'mah catches fire, leading to a dramatic intervention by Byng, which further entwines the lives of the characters. This opening sets up a narrative filled with ambitious pursuits, personal conflicts, and looming societal tensions in which these characters must navigate their desires and decisions. (This is an automatically generated summary.)
Release date is 2003-02-01
Produced by Juli Rew. HTML version by Al Haines.
Keywords: South African War, 1899-1902 -- Fiction; Married people -- Fiction; Triangles (Interpersonal relations) -- Fiction; Man-woman relationships -- Fiction